Outdoor Learning Activity in Teaching Students’ Descriptive Writing Skills - Hadi, Muhamad Sofian; Mutiarani, Mutiarani; Herlina, Sri (JOLLT Journal of Languages and Language Teaching, 2021)
This study aims to find out the effectiveness of the outdoor learning method to improve students’ writing skills at senior high schools. The concept of the outdoor learning method in this study adopts collaborative writing learning activities. The learning activities are carried out outside writing classes. The research method is a quantitative method with a Pre-Experimental design using pre-test and post-test design. The instrument in collecting the data uses writing tests. The researcher only used one class of ninth-graders of SMP IT HARAPAN. The sampling technique used was random cluster sampling in which the 9th-grade students as the population participated as the sample. The data were analyzed statistically using a t-test. Based on the analysis results, the average value obtained in the pre-test was 42,22, and the post-test was 76,60. Meanwhile, the score of the t-test was 37,27, and the t-table was 1,706 with a significant 5% (0.05). It means the score of the t-test was greater than the t-table. So, the alternative hypothesis (H1) was accepted, and the null hypothesis (H0) was rejected. It can be concluded that Outdoor learning activities can facilitate students to improve their writing skills.